(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Like other SCADA systems in Central Java & DIY APD, there are three main SCADA implementation pillars: Master Station, Remote Terminal Unit, and Telecommunications. The Master Station functions to manage the SCADA software and its operational display. The remote Terminal Unit is an executor device to control and retrieve the status of Electric Power Distribution equipment. Meanwhile, Telecommunications is in charge of managing communication to connect the results of the Remote Terminal Unit with the Master Station. To optimize all three and improve the reliability of electricity distribution PT. PLN (Persero) Distribution Control Area (APD in Indonesian) Central Java and DIY changed the current SCADA configuration (still separate in each region) into a centralized and well-organized future structure. The stages of realizing the plan include: setting up the SCADA master configuration, namely ROPO, IDAS, and "Survalent"; Building a backup server (Quad Redundant Server); and embodying the concept of 3 DCC.